Efficacy and safety of long-pulse pulsed dye laser delivered with compression versus cryotherapy for treatment of solar lentigines - Hassan Seirafi; Soheil Fateh; Farshad Farnaghi; Amir H Ehsani; Pedram Noormohammadpour (Wolters Kluwer Medknow Publications, 2011)
Background: Although cryotherapy is still the first-line therapy for solar lentigines, because of the side effects such as post-inflammatory hyperpigmentation (PIH), especially in patients with darker skin types, pigment-specific lasers should be considered as a therapy for initial treatment. Aim: The aim of this study is to evaluate the efficacy and safety of cryotherapy compared with 595-nm pulsed dye laser (PDL) with cutaneous compression in the treatment of solar lentigines. Materials and Methods: Twenty-two patients (skin type II−IV) with facial or hand lentigines participated in this study. Lesions of one side of the face or each hand were randomly assigned and treated with either cryotherapy or PDL. Treatments were performed with radiant exposures of 10 J/cm 2 , 7-mm spot size and 1.5 ms pulse duration with no epidermal cooling. Photographs were taken before treatment and 1-month later. The response rate and side effects were compared. Results: PDL was more likely to produce substantial lightening of the solar lentigines than cryotherapy, especially in skin type III and IV (n = 8, n = 9; P < 0.05), but might be no difference in type II (n = 5; P > 0.05). PIH was seen only in cryotherapy group. PDL group had only minimal erythema. No purpura was observed. Conclusion: PDL with compression is superior to cryotherapy in the treatment of solar lentigines in darker skin types.